2004
DOI: 10.1074/jbc.m403552200
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Functions of the Novel Serine/Threonine Kinase Ndr2

Abstract: We have identified a novel member of the Ndr subfamily of serine/threonine protein kinases, Ndr2, as a gene product that is induced in the mouse amygdala during fear memory consolidation and examined a possible function of this kinase in neural differentiation. Expression of Ndr2 mRNA was detected in various cortical and subcortical brain regions, as well as non-neuronal tissues. Its expression in the amygdala was increased 6 h after Pavlovian fear conditioning training and returned to control levels within 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
56
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 28 publications
5
56
0
Order By: Relevance
“…Similar to the observation in the filamentous fungus, PKA in animal cells has been shown to promote a round cell shape during cytokinesis and to phosphorylate monomeric actin to prevent actin-fiber formation (Ohta et al, 1987;Prat et al, 1993). The fact the animal NDR kinase function has been implied in regulating actin organization (Geng et al, 2000;Zallen et al, 2000;Emoto et al, 2004;Stork et al, 2004) along with the stated effect of PKA on the cytoskeleton in a variety of organisms supports the possibility that the fungal components function in a similar manner. It is conceivable that COT1/POD6 may positively modulate actin dynamics in parallel to the negatively acting PKA pathway.…”
Section: Discussionmentioning
confidence: 58%
“…Similar to the observation in the filamentous fungus, PKA in animal cells has been shown to promote a round cell shape during cytokinesis and to phosphorylate monomeric actin to prevent actin-fiber formation (Ohta et al, 1987;Prat et al, 1993). The fact the animal NDR kinase function has been implied in regulating actin organization (Geng et al, 2000;Zallen et al, 2000;Emoto et al, 2004;Stork et al, 2004) along with the stated effect of PKA on the cytoskeleton in a variety of organisms supports the possibility that the fungal components function in a similar manner. It is conceivable that COT1/POD6 may positively modulate actin dynamics in parallel to the negatively acting PKA pathway.…”
Section: Discussionmentioning
confidence: 58%
“…In particular, worm and fly NDR kinases have been shown previously to play central roles in neuronal processes (6,7). However, a recent report suggests that the murine NDR2 form also plays an Thus, it will be essential to test how much localized activation of NDR on the plasma membrane contributes to the neuronal functions described by Stork et al (21). Nevertheless, our work provides important information relevant to the role of NDR in cancer biology.…”
Section: Discussionmentioning
confidence: 80%
“…Although the basic mechanism of activation of human NDR protein kinase in vitro has been described in detail (3,16,20,23), the regulation of NDR in a cellular context still remains to be elucidated. Such information should bring insight into its cellular functions and, in particular, into its possible role in cancer.While NDR1 was reported to be localized predominantly in the nucleus (14), NDR2 was shown very recently to be mostly excluded from the nucleus, displaying a cytoplasmic distribution (4,5,20,21). This observation is intriguing given the high sequence similarity between these two kinases.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, the hippocampal formation processes multimodal information concerning contexts that define the time and place of aversive experiences during fear conditioning . Cellular and molecular correlates of synaptic plasticity as well as network activity patterns in these structures have been identified that relate to the formation of short-term and long-term fear memories (Adamec 2000;Buzsáki 2002;Paré et al 2002;Pelletier and Paré 2004;Santini et al 2004;Stork et al 2004). Specifically, increased theta synchronization between the amygdala and hippocampus has been postulated as a neural correlate of long-term cued fear memory (Seidenbecher et al 2003;Narayanan et al 2007).…”
mentioning
confidence: 99%